Experience of Education in the International Classroom-A Systematic Literature Review - Safipour, Jalal; Wenneberg, Stig; Hadziabdic, Emina (Journal of International Students, 2018)
In this essay, we investigate the learning and teaching experiences in the international classroom from both the teachers and the students’ perspectives. The findings of this study showed that language barriers are one of the difficulties, but academic cultural differences seem to play a more important role that can impact on the learning outcomes in the international classroom. This can also lead to negative experiences and the forming of stereotypical views of international students solely based on their educational background.